Revision of Hellwigiella Szépligeti, 1905 (Hymenoptera, Ichneumonidae, Ophioninae), with revalidation of H. nigripennis Szépligeti, 1905 - Lima, Alessandro Rodrigues (Zootaxa, 2018)
The taxonomic history of Hellwigiella Szépligeti is presented with comments. Ophion similis (Szépligeti, 1905) is diagnosed and illustrated, with the first record for Morocco. Hellwigiella is redescribed and illustrated, with comments on its differentiation from O. similis. A key to the two valid species, H. dichromoptera and H. nigripennis stat. rev., is provided.